Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM - Melifia Liantifa; Anggia Ayu Lestari; Iin Syofia Yandra (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
This community service activity is based on the low utilization of digital marketing among micro, small and medium enterprises (MSMEs) in Siulak Kecil Mudik Village. The main problems include limited branding knowledge, packaging design, and the use of digital media for marketing. The purpose of this activity is to improve MSME actors’ ability in building brand identity and optimizing digital marketing strategies. The methods used include observation, training, mentoring, and technical guidance on digital marketing through social media such as Instagram, WhatsApp Business, Google Business, and simple websites. The results show an improvement in participants’ ability to create brand identity, improve product packaging, and actively use social media for promotion. This activity enhances local product competitiveness and expands market reach.